2020
DOI: 10.7717/peerj.8623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auxin derivatives on phenotypic plasticity and stress tolerance in five species of the green algaDesmodesmus(Chlorophyceae, Chlorophyta)

Abstract: Green microalgae of the genus Desmodesmus are characterized by a high degree of phenotypic plasticity (i.e. colony morphology), allowing them to be truly cosmopolitan and withstand environmental fluctuations. This flexibility enables Desmodesmus to produce a phenotype–environment match across a range of environments broader compared to algae with more fixed phenotypes. Indoles and their derivatives are a well-known crucial class of heterocyclic compounds and are widespread in different species of plants, anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…These results highlight the phenotypic plasticity of S. marinoi when submitted to different light conditions, with ovothiol involvement into the photoresponse when cells cope with natural high light condition (sinusoidal), while it does not take part to the response of cells to unnatural high light condition. This is a quite interesting issue being that phenotypic plasticity, defined as the ability of an organism's genotype to display different phenotypes in response to the environmental variability, is a key process explaining microalgal adaptability to natural conditions [57][58][59]. In particular, microalgae are adapted to a natural light sinusoidal distribution during the day, allowing them to efficiently cope with light variations, e.g., high light environment, through the activation of different kinds of complementary photoresponses, from the fast non-photochemical quenching or xanthophyll cycle operation to changes in carotenoids levels or in antioxidant network activation.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the phenotypic plasticity of S. marinoi when submitted to different light conditions, with ovothiol involvement into the photoresponse when cells cope with natural high light condition (sinusoidal), while it does not take part to the response of cells to unnatural high light condition. This is a quite interesting issue being that phenotypic plasticity, defined as the ability of an organism's genotype to display different phenotypes in response to the environmental variability, is a key process explaining microalgal adaptability to natural conditions [57][58][59]. In particular, microalgae are adapted to a natural light sinusoidal distribution during the day, allowing them to efficiently cope with light variations, e.g., high light environment, through the activation of different kinds of complementary photoresponses, from the fast non-photochemical quenching or xanthophyll cycle operation to changes in carotenoids levels or in antioxidant network activation.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the IAA pretreatment may also be a factor. The durations of IAA pretreatments used in previous studies varied by organism, with durations of 2 h for prokaryotic bacteria ( Bianco et al , 2006 ), 3 h for rhizobia ( Donati et al , 2013 ), 24 h for algae ( Lin et al , 2020 ), and 12 h for yeast ( Sun et al , 2014 ). The durations of the IAA pretreatment used in the present study (24 and 48 h) were sufficient to trigger ethanol tolerance; however, further studies are needed to clarify how the duration of the pretreatment may affect this response.…”
Section: Discussionmentioning
confidence: 99%
“…and promoted the accumulation of lipid droplets in algal cells, an effect that is related to stress tolerance ( Chung et al , 2018 ). Follow-up studies confirmed that stress tolerance was enhanced in green algae treated with IAA ( Lin et al , 2020 ). Similar mechanisms have been detected in bacteria.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, these variations will also depend on the species and its adjustment mechanisms to osmotic stress. For example, in the case of Botryococcus braunii, the increase in salinity allowed a greater production of polysaccharides [59]. Therefore, the increase in EPS production in T. suecica will depend on the cultivation condition, abiotic factors such as salinity and optimization of EPS extraction methods.…”
Section: Production and Extraction Of Exopolysaccharides (Eps) Of Autotrophic And Heterotrophic Biomass Cultures Of T Suecicamentioning
confidence: 99%